Influence of Different Polypeptides Fractions Derived from Sus Scrofa Immune Organs on the Rats Immunological Reactivity - L.V. Fedulova; Е.R. Vasilevskaya; Е.А. Kotenkova; A.A. Elkina; M.G. Baryshev; A.B. Lisitsyn (Journal of Pharmacy and Nutrition Sciences, 2017)
The influence of protein-peptide compounds, extracted with deuterium water as solubilizer agent from mixture of Sus scofa thymus, spleen and lymph nodes extracts, was carried out on Wistar rats with cytostatic-induced immunodeficiency model. Intragastric administration of extract fraction with molecular weight more than 30 kDa, did not lead to significant changes. Thus, polypeptide compounds with molecular weight less than 30 kD, extracted from Sus scofa immune organs, significantly increased T-lymphocytes amount, affected macrophages system by T-helper (CD4) stimulation and activated cycle of complementary cascade. Differences between the experimental results in T-helper synthesis activation (CD4) in animals treated with the medium and low molecular weight fractions can be explained by the ability of biomolecules having a molecular weight less than 30 kDa (in particular, isolated from the spleen, which, in its cellular structure contains key regulatory factors) to change the speed of cell differentiation.